KUALITAS DAGING ITIK YANG DIRENDAM JUS BUAH NANAS (ANANAS COMASUS L. MERR) : EFFECT OF GIVING PINEAPLLE JUICE (ANANAS COMASUS L. MERR) ON QUALITY OF DUCK MEAT - Runi; Wijinindyah, Ayutha; Wulandari, Lies Tiarini (Universitas Muhammadiyah Malang, 2023)
Duck meat is a source of animal protein. Duck meat is widely used in various food preparations. The aim of this research was to determine the effect of giving pineapple juice on the physical and chemical quality of duck meat. The experimental design used complete randomization with four treatments and three replications. The treatments applied were : P0 : duck meat (without the additional of pineapple juice), P1 : duck meat + 25% pineapple juice, P2 : duck meat + 50% pineapple juice, P3 : duck meat + 75% pineapple juice. The data obtained was analysed using analysis of variance (ANOVA) and continued with wether three was a real influence. The variables observed include physical (pH) and chemical quality (water content, protein content and fat content). The result showed that giving pineapple juice to duck meat had a significant effect (P<0,05) on the quality of pH and water content, but thre was no significant difference (P>0,05) on protein and fat content of duck meat. Providing pineapple juice up to 50% can reduce the pH and water content, while up to 75% it has no effect on the protein and fat of duck meat.